-11:3+3×(-2)-5 repede vaa rooooog
Răspunsuri la întrebare
Răspuns de
1
-11:3+3×(-2)-5 = - 11/3 - 6 - 5 = = -11/3 - 18/3 - 15/3 = -44/3 = - 14,(6)
Răspuns de
0
-11:3+3×(-2)-5 =
= -11 : 3 + (-6) -5 =
= -11/3 - 6 -5 =
= -11/3 -11 =
= (-11-33)/3 =
= -44/3 =
= - 14,(6)
= -11 : 3 + (-6) -5 =
= -11/3 - 6 -5 =
= -11/3 -11 =
= (-11-33)/3 =
= -44/3 =
= - 14,(6)
Alte întrebări interesante
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă